Microbial Profiling, Bioremediation of Cadmium and Dye Decolourization Competence of Marine Bacterial Isolates - Teja, M.; Kumar, D. Muni; Bindiya, P.; Sudhakar, G. (New Innovations in Chemistry and Biochemistry Vol. 7, 2022)
One of the diverse communities of the marine environment is the microbial community. Microorganisms isolated from the marine environment have been shown in studies to be metabolically active and to have adapted to life in the ocean. Marine microorganisms use a variety of survival strategies to combat heavy metal stress and decolorization of various textile dyes, thus playing an important role in cadmium bioremediation and textile dye degradation. The current study focuses on the isolation and 16S rRNA molecular characterization of M3, M8 bacterial strains isolated from marine water samples collected from Visakhapatnam harbour. M3 and M8 isolates were also tested for their ability to remove cadmium from the environment and decolorize various textile dyes.The water sample was used to isolate bacterial strains using the tube dilution method, and ten different isolates were screened. Biochemical tests were performed on the isolates to validate them, as well as 16S rRNA molecular sequencing and phylogenetic analysis to identify the species. Two bacterial strains, M3 and M8, were subjected to 16srRNA molecular sequencing and phylogenetic analysis and were identified as Bacillus subtilis and Pseudomonas resinovorans, respectively. When tested with nine different textile dyes with wavelengths ranging from 400 to 600nm, the two bacterial strains demonstrated promising dye degradation properties as well as removal of cadmium from the growth medium. The current study demonstrates that the isolates M3 and M8 are potential strains for dye decolorization and cadmium bioremediation applications.